Trabalho, Cultura e produção cultural: notas para uma sociologia do trabalho com arte e cultura no Brasil - André Grillo (Ciências Sociais Unisinos)
Studies on culture and art and on the “world of work” are often found in separate fields, although some reference works on the art professions, art production chain and the labor market of artists such as those from Howard Becker and Pierre-Michel Menger. In order to analyze cultural production in the so-called “new world of work”, and the category of cultural producer in contemporary Brazil, I seek to develop a sociology of work with art and culture, making use of the theoretical framework of the sociology of work based on the analysis of André Gorz’s and Boltanki and Chiapello on contemporary changes in the world of work (and the influence of the counterculture in this process), complementing them with the sociology of work with art and culture of Menger and Becker. For that reason, I begin with the discussion about the so-called “new world of work” from the perspectives of the evolution of Gorz’s thought and Boltanski and Chiapello’s classic The New Spirit of Capitalism. Next, I present Menger’s approach to labor markets with culture and art, bringing his analysis closer to those discussed earlier, and complementing it with Becker’s study Worlds of Art. From then on, I try to think about the work with culture and art in contemporary Brazil from the perspective of “cultural producers”.